A FRAMEWORK TO IMPROVE ENVIRONMENTAL PERFORMANCE IN SMES - Marudut Sirait (Journal of Engineering and Management in Industrial System, 2017)
The aim of this study is to develop a conceptual framework for assessing and minimzing industrial waste. A conceptual framework is developed by integrating Life Cycle Assessment (LCA) tool and cleaner production method. LCA is utilized to evaluate and identifi  industrial waste along the life cycle of product/services . On the other hand,  cleaner production method is implemented for mitigation strategy to minimizing the most significant waste along industrial activities. By using LCA, the significant waste will be identified. Furthermore, cleaner production will be implemented to the significant waste to improve the environmental performance of industries activities. Cleaner production strategies such as product modification, Input substitution, technology modification, reuse/recycling, and good housekeeping are applied to prevent industrial waste generation. Furthermore, the integration betwen LCA tool and CP method significanly improve the environmnetal performance  during the industrial activities. CP and LCA were succesfull for improving environmental performance in term of raw material saving, water saving, energy saving and wastewater reduction.